PERANCANGAN ANTENA MIKROSTRIP ARRAY CLOVER PATCH PADA FREKUENSI 2,4 GHZ - Dandy Imam Zaki; Rudy Yuwono; Muhammad Fauzan Edy Purnomo (Jurnal Mahasiswa TEUB, 2020)
Abstract—- Microstrip antenna is one type of antenna that has been widely used in laboratories in universities because it is practical and easy to produce. The author uses different amount of clover-shaped patch on two different microstrip antenna with 1×1 and 2×2 format to analyze the parameters on 2.4 GHz operation frequency. Parameter which been analyzed are VSWR, return loss, and bandwidth. In conclusion, the addition of radiating element (patch) of the antenna lower the antenna’s performance in VSWR and Return Loss, but widen the bandwidth of the antenna.Index Terms—Microstrip Antenna, Array Antenna, Clover shaped Patch